2023
DOI: 10.3390/ani13132219
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Output Reveals the Maternal Effects on Offspring Size-Number Trade-Off in Cultured Asian Yellow Pond Turtle (Mauremys mutica)

Abstract: Offspring size-number trade-off is a critical component of life-history theory and is important for further understanding the reproductive strategies of animals. The relationship between this trade-off and maternal size has been explored in several turtle species, except for the Asian yellow pond turtle, Mauremys mutica. To investigate how the maternal condition affects offspring size and number, we explored the relationships among the maternal body size and the number and size of cultured M. mutica hatchlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Some females had little or no offspring during the 4 years, while others had a high reproductive capacity. We also found that the number of offspring per female increased with the maternal plastron length rather than age [35]. These results suggest that paternity testing can be used to analyze differences in female fecundity, select females with high and stable fecundity and eliminate females with low fecundity, thus serving as the next step in the selection of highly fecund turtles (Table S3).…”
Section: Discussionmentioning
confidence: 58%
“…Some females had little or no offspring during the 4 years, while others had a high reproductive capacity. We also found that the number of offspring per female increased with the maternal plastron length rather than age [35]. These results suggest that paternity testing can be used to analyze differences in female fecundity, select females with high and stable fecundity and eliminate females with low fecundity, thus serving as the next step in the selection of highly fecund turtles (Table S3).…”
Section: Discussionmentioning
confidence: 58%